2021
DOI: 10.3389/fcimb.2021.622474
|View full text |Cite
|
Sign up to set email alerts
|

The Vaginal Microbial Signatures of Preterm Birth Delivery in Indian Women

Abstract: BackgroundThe incidence of preterm birth (PTB) in India is around 13%. Specific bacterial communities or individual taxon living in the vaginal milieu of pregnant women is a potential risk factor for PTB and may play an important role in its pathophysiology. Besides, bacterial taxa associated with PTB vary across populations.ObjectiveConduct a comparative analysis of vaginal microbiome composition and microbial genomic repertoires of women who enrolled in the Interdisciplinary Group for Advanced Research on Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 90 publications
2
32
0
Order By: Relevance
“…This was also demonstrated by Kindinger et al., who reported that the vaginal microbiome dominated by L. iners at 16 weeks of gestation is a risk factor for both a short cervix and early PTB (<34 weeks), whereas L. crispatus dominance is protective against PTB in a more ethnically diverse cohort ( Kindinger et al., 2017 ). Recent studies from different countries also showed a significant association between L. iners and an increased prevalence of PTB ( Elovitz et al., 2019 ; Aslam et al., 2020 ; Goodfellow et al., 2021 ; Kumar et al., 2021 ; Payne et al., 2021 ; Sarmento et al., 2021 ). However, several studies reported no significant association between L. iners and PTB ( Callahan et al., 2017 ; Blostein et al., 2020 ; Witkin et al., 2021 ).…”
Section: Iners and Women Diseasesmentioning
confidence: 87%
See 1 more Smart Citation
“…This was also demonstrated by Kindinger et al., who reported that the vaginal microbiome dominated by L. iners at 16 weeks of gestation is a risk factor for both a short cervix and early PTB (<34 weeks), whereas L. crispatus dominance is protective against PTB in a more ethnically diverse cohort ( Kindinger et al., 2017 ). Recent studies from different countries also showed a significant association between L. iners and an increased prevalence of PTB ( Elovitz et al., 2019 ; Aslam et al., 2020 ; Goodfellow et al., 2021 ; Kumar et al., 2021 ; Payne et al., 2021 ; Sarmento et al., 2021 ). However, several studies reported no significant association between L. iners and PTB ( Callahan et al., 2017 ; Blostein et al., 2020 ; Witkin et al., 2021 ).…”
Section: Iners and Women Diseasesmentioning
confidence: 87%
“…Earlier studies confirmed that high estradiol levels and the consequent high glycogen levels in the vagina during pregnancy result in stronger vaginal acidification, thereby promoting the prevalence of Lactobacillu s species as gestation progresses ( Aagaard et al., 2012 ; Basavaprabhu et al., 2020 ). However, many studies have indicated that the L. iners -dominated vaginal microbiome was more likely to shift towards dysbiosis during pregnancy ( Mls et al., 2019 ; Kumar et al., 2021 ; Sarmento et al., 2021 ). In our previous study, we found that the abundance of L. iners decreased significantly in the second and third trimester, whereas that of L. crispatus increased in the second trimester compared with the first trimester in healthy pregnant women ( Zheng et al., 2019 ).…”
Section: Iners and Women Diseasesmentioning
confidence: 99%
“…As for L. gasseri, it is significantly higher in women who delivered term babies compared to those who delivered preterm 30 . The presence of secretory transcriptional regulator and several ribosomally synthesized antimicrobial peptides reported by genomic analysis correlated with L. gasseri anti-inflammatory condition in the vagina.…”
Section: Discussionmentioning
confidence: 95%
“…These Lactobacillusdominant CSTs (CSTs I-III, and V) are generally perceived as being conducive to reproductive health. Conversely, the relationship between human reproductive health and the non-Lactobacillus-dominant, and thus species rich and diverse, CST IV is more ambiguous (45,(55)(56)(57)(63)(64)(65). This disparity in health outcome potentially related to the structure of the vaginal microbiota is highlighted by the observation that women who do not have a Lactobacillus-dominant vaginal microbiota prior to or during early pregnancy typically transition to a vaginal microbiota of Lactobacillus-dominance as gestation progresses (50,51,66), suggesting that pregnancy entails selective pressures for Lactobacillus-dominance in the vaginal microenvironment.…”
Section: Abstract: Pregnancy Mouse Model Microbiome Rodentibacter Ora...mentioning
confidence: 99%